A Review on Ethnobotanical Insights into the Medicinal Potential in District of Himachal Pradesh, India - Koundal, Anchal; Attri, Lucky K (Asian Journal of Biological and Life Sciences, 2025)
Background: Himachal Pradesh is a hilly state in Northwest India composed of a rich legacy of natural resources and ethnobotanical flora. This study examined the ethnomedicinal potential of the flora in several districts of Himachal Pradesh, an area rich in traditional healing practices and biodiversity. Objectives: The objective of this review was to encourage the sustainable utilization of the ethnomedicinal flora of Himachal Pradesh, emphasizing its potential for bioprospecting and cultural preservation. It aims to guarantee the ongoing relevance and preservation of these priceless biological treasures by encouraging cooperation between the local people and academics. Materials and Methods: An ethnomedicinal review of Himachal Pradesh was conducted through the texts, research articles related to ethnomedicinal and traditional uses, phytochemistry, and therapeutic activities available on Pubmed, Science Direct, Google Scholars, Scopus, and Web of Science etc. Results: The study explores the distinct therapeutic applications of plant species that are employed by the local population to cure maladies, varying from respiratory problems to digestive disorders. This study highlighted the importance of wild plants for various purposes, including medicine, in this remote high-altitude region. The study also highlights the specialized knowledge and application of medicinal plants for specific health conditions in the region. Conclusion: Different plant species are displayed in each district, reflecting the differences in altitude, climate, and cultural customs. It also addresses issues such as habitat loss, climate change, and loss of traditional knowledge, highlighting the significance of conservation efforts. There is a noticeable decline in traditional knowledge, particularly among younger generations, due to modernization and changing lifestyles.
Keywords: ethnomedicine; Flora; Himachal Pradesh; Medicinal plants; Traditional Health Practices